2010
DOI: 10.1111/j.1365-2915.2009.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

The housefly,Musca domestica, as a possible mechanical vector of Newcastle disease virus in the laboratory and field

Abstract: Abstract. Newcastle disease (Paramyxoviridae) is a highly infectious virus shed in the faeces of infected birds. Non-biting Muscid flies characteristically visit manure and decaying organic material to feed and oviposit, and may contribute to disease transmission. The housefly, Musca domestica (Linnaeus, 1758) (Diptera: Muscidae), has been implicated as a mechanical vector of numerous pathogens. In this study 2000 aerial net-captured houseflies were examined for their ability to harbour Newcastle disease virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…al., 2008;BARIN et al, 2010), besides being responsible for the production of myiasis in humans and animals (ZUMPT, 1985). The immature stages of some species of these flies develop in animal and plant decaying organic matter such as feces, garbage, corpses and carrion (GRABOVAC & PETRIĆ, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…al., 2008;BARIN et al, 2010), besides being responsible for the production of myiasis in humans and animals (ZUMPT, 1985). The immature stages of some species of these flies develop in animal and plant decaying organic matter such as feces, garbage, corpses and carrion (GRABOVAC & PETRIĆ, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…House flies, occur throughout the tropics and are also found in warm temperate regions and some cooler areas. It is recognized as a serious public health pest to human beings and livestock by transmitting many infectious diseases causing a serious threat to human and livestock by vectoring several pathogenic organisms such as protozoa cysts, helminth parasites, enteropathogenic bacteria, and enterovirus [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The vector potential of M. domestica has been proved for the propagation of protozoan (amoebic dysentery), bacterial (shigellosis, salmonellosis, cholera), helminthic (round worms, hookworms, pinworms and tapeworms), viral (Turkey Corona virus, Reticuloendotheliosis virus, H5N1 influenza virus) and rickettsial infections, among others [4]. The study by Barro et al [6], revealed M. domestica to be predominant fly associated with street-food vendors in Ouagadougou which carried isolates of Coliform, Salmonella, Shigella, Staphylococci and Streptococci on both their legs and proboscis, while Barin et al [7], demonstrated presence of Newcastle disease virus in the significant number of adult muscid flies collected from 20 poultry farms near Tehran, Iran. Furthermore, recent reports about carriage of antibiotic-resistant pathogens by M. domestica collected from different fast-food restaurants in northern Kansas (USA) [8] and in hospitals of several countries of Sub-Saharan Africa [9] are quite alarming and calls for urgent M. domestica control measures.…”
Section: Introductionmentioning
confidence: 99%